Study of the dependence of the intensity of vibration treatment on the location of the exciter - Николаенко, А. П.; Калмыков, М. А. (Eastern-European Journal of Enterprise Technologies, 2009)
The motion of fluid elements in vibration machines is considered in the article, the calculated values ​​of the circulation rate depending on the location and stability of the excitercirculatory motion are leaded